Analisis Sistem Usahatani Rumput Laut di Desa Bungin Permai Kecamatan Tinanggea Kabupaten Konawe Selatan - Dewi, Diah Puspita; Fausayana, Ine; Yusria, Wa Ode (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2017)
The purpose of this research is to know: (1) income obtained from seaweed business in Bungin Permai Village, Tinanggea Subdistrict, South Konawe Regency (2) seaweed farming in Bungin Permai Village, Tinanggea Sub-District, South Konawe Regency. This research uses qualitative and quantitative methods. The population of this study is 233 seaweed farmers. The sample determination uses simple random sampling technique. The number of samples in this study were 37 respondents, thesample size was determined by referring to the Slovin formula. The results of this study indicate (1) The average income of farmers respondents on seaweed farming in one production process that is Rp11.412.683 (2) With R / C of 7.353 means seaweed farming profitable and feasible to be developed and the use of production costs efficient.